2014
DOI: 10.1017/jfm.2014.519
|View full text |Cite
|
Sign up to set email alerts
|

A dual-tube model for gas dynamics in fractured nanoporous shale formations

Abstract: Gas flow through fractured nanoporous shale formations is complicated by a hierarchy of structural features (ranging from nanopores to microseismic and hydraulic fractures) and by several transport mechanisms that differ from the standard viscous flow used in reservoir modelling. In small pores, self-diffusion becomes more important than advection; also, slippage effects and Knudsen diffusion might become relevant at low densities. We derive a nonlinear effective diffusion coefficient that describes the main t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 27 publications
(30 reference statements)
7
56
0
Order By: Relevance
“…The MFR obtained from the Boltzmann equation is a key parameter in the generalized Reynolds equation to describe gas-film lubrication problems such as the gas slide bearing (Fukui & Kaneko 1987, 1990Cercignani, Lampis & Lorenzani 2007), as well as in the upscaling methods used to predict the gas permeability of ultra-tight shale strata (Darabi et al 2012;Mehmani, Prodanović & Javadpour 2013;Lunati & Lee 2014;Ma et al 2014).…”
mentioning
confidence: 99%
“…The MFR obtained from the Boltzmann equation is a key parameter in the generalized Reynolds equation to describe gas-film lubrication problems such as the gas slide bearing (Fukui & Kaneko 1987, 1990Cercignani, Lampis & Lorenzani 2007), as well as in the upscaling methods used to predict the gas permeability of ultra-tight shale strata (Darabi et al 2012;Mehmani, Prodanović & Javadpour 2013;Lunati & Lee 2014;Ma et al 2014).…”
mentioning
confidence: 99%
“…GRI permeability acquisition) because it does not take into account slip flow and Knudsen (and Fickian) diffusion through the pore space and kerogen [32], [21], and [33]; however, we expect that…”
Section: Fluid Flow Simulations With the Lattice-boltzmann Methodsmentioning
confidence: 99%
“…Further, if the porous media was a strong adsorbent and the pore diameter was nano-scale, the bulk transport of gas molecules would be strongly influenced by the adsorption potential of the walls, and surface diffusion would became dominant [17,23,29]. For pure gas diffusing in porous media [20,72], the formulas of the above three diffusion types were displayed in Eqs. (11)-(13):…”
Section: Comparison Of Diffusion Coefficient and Mechanismmentioning
confidence: 99%
“…Considering the large percentages of adsorbed gas, its flow behavior has become one of the key transport mechanisms which needed deep research. Reservoir simulations also demonstrated that both the well productivity and accumulative production of shale gas reservoirs would present a remarkable increase if the output of adsorbed gas were involved [19][20][21].…”
Section: Introductionmentioning
confidence: 98%